2013
DOI: 10.1002/pon.3323
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and correlates of supportive care needs in testicular cancer survivors: a cross‐sectional study

Abstract: Objective: This cross-sectional study aimed to identify the prevalence and correlates of supportive care needs in testicular cancer (TC) survivors. Methods:Men who had completed active anti-cancer treatment for TC between 6 months and 5 years previously showing no evidence of recurrence were recruited from 14 Australian cancer centres (September 2009 -February 2011. Participants completed a self-report questionnaire measuring sociodemographics, disease and treatment information, supportive care needs (CaSUN), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 28 publications
6
83
3
4
Order By: Relevance
“…Eighteen suitable datasets were obtained [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Table 1 summarises their characteristics and the number of observations each contributed to various psychometric analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen suitable datasets were obtained [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Table 1 summarises their characteristics and the number of observations each contributed to various psychometric analyses.…”
Section: Resultsmentioning
confidence: 99%
“…In 2013, an Australian study reported that among 244 testis cancer survivors completing a survey, 66% had one or more unmet supportive care needs [15]. The average number was 4.7, and life stress and relationship issues figured prominently.…”
Section: Qol Studiesmentioning
confidence: 98%
“…Many cancer survivors also report having unmet information and support needs in dealing with these issues (Geller, Vacek, Flynn, Lord, & Cranmer, 2014; Hodgkinson, Butow, Fuchs, et al., 2007; Hodgkinson, Butow, Hunt, et al., 2007; Willems et al., 2016a). The greater the number of unmet information and support needs, the greater the depressive feelings, fear of recurrence and distress, and the lower the quality of life of cancer survivors (Smith et al., 2013). Insight into these unmet needs may help agenda‐setting in health policy addressing cancer survivors unmet needs, tailoring information provision and development of tailored interventions.…”
Section: Introductionmentioning
confidence: 99%
“…For our two studies (Kanera, Bolman, Mesters, et al., 2016; Willems et al., 2016a), the validated CaSUN was regarded as the most appropriate general questionnaire to specifically investigate the unmet needs of cancer survivors (Bender et al., 2012; Brennan, Butow, Spillane, & Boyle, 2016; Geller et al., 2014; Harrison et al., 2011; Hodgkinson, Butow, Fuchs, et al., 2007; Hodgkinson, Butow, Hunt, et al., 2007; Rowlands, Janda, McKinnon, Webb, & Beesley, 2015; Smith et al., 2013; Urbaniec, Collins, Denson, & Whitford, 2011). Therefore, the CaSUN was translated into Dutch.…”
Section: Introductionmentioning
confidence: 99%